Perengkahan PFAD (Palm Fatty Acid Destillate) Untuk Menghasilkan Biofuel Menggunakan Katalis Ni-Mo/Zeolit - Setiawan, Rudi; Zahrina, Ida; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Petroleum reserves are depleted in Indonesia along with increased fuel requirements, demanding Indonesian society to harness alternative energy, one of which is biofuel. In this study, biofuels produced from cracking fatty acids contained in Destillate Palm Fatty Acid (PFAD). PFAD converted into biofuels via catalytic cracking process using a catalyst Ni.Mo / Zeolite with reaction temperature 380 oC in a stirred batch reactor. Metal concentrations in the zeolite was varied at 0%, 0.5%, 1% and 1.5% and the variation of the reaction stirring 300 rpm, 400 rpm, 500 rpm and 600 rpm. Cracking process using nitrogen gas with a flow rate of 150 ml / min. Yield (%) of the product obtained at the maximum stirring speed of 500 rpm with a metal concentration of 1%, amounting to 71.43% or 125 ml with 31.53% biofuel conversion. The composition of biofuels on cracking products was 8.8% and 35% Gasoline Kerosene and Diesel.  Key Words: Biofuel, Catalytic Cracking, Ni.Mo/Zeolite, PFAD